EFFECT OF EDUCATION AND TRAINING ON PERFORMANCE IN MEDIATION OF VILLAGE APPARATUS WORK MOTIVATION IN SEKATAK DISTRICT, BULUNGAN REGENCY - Roni Paembonan; Ana Srie Kaningsih; Lina Warlina; Chong Pikbee (STKIP Singkawang, 2021)
The purpose of this study is to prove the effectiveness of education and training on the performance in the mediation work motivation Sekatak apparatus village in the district of Bulungan. This type of research is explanatory research. Population and sample it is the entire staff of village officials in the district Bulungan Sekatak as many as 124 people, with the technique of total sampling. The data analysis technique used in this study uses a Path Analysis approach. The results showed that the education and training had a positive and significant effect on the work motivation of village apparatus employees. The education and training positive and significantly effect on the performance of employees of village officials. Work motivation has a positive and significant effect on the performance of village apparatus employees. Work motivation as a mediating variable between education and training on the performance of village apparatus employees in Sekatak District, Bulungan Regency.